2016
DOI: 10.4149/bll_2016_045
|View full text |Cite
|
Sign up to set email alerts
|

High cholesterol diet leads to oxidant load and peroxidation in the rabbit kidney tissue

Abstract: OBJECTIVES: The aim of this study was to investigate possible effects of high cholesterol diet on oxidant/antioxidant status in rabbit kidney tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Furthermore, some studies in rabbits examined the effect of high cholesterol diets in rabbits and found a significant reduction in SOD [31,32] which is concordance to the results in this study. A study that showed an increase in MDA [32] in rabbits utilized dietary cholesterol at higher concentration in the diet compared to this study using 1% w/w in contrast to this study where 0.5% w/w was utilized.…”
Section: Hematoxylin and Eosin (A) Liver From Rabbit Fed Normal Chowsupporting
confidence: 91%
“…Furthermore, some studies in rabbits examined the effect of high cholesterol diets in rabbits and found a significant reduction in SOD [31,32] which is concordance to the results in this study. A study that showed an increase in MDA [32] in rabbits utilized dietary cholesterol at higher concentration in the diet compared to this study using 1% w/w in contrast to this study where 0.5% w/w was utilized.…”
Section: Hematoxylin and Eosin (A) Liver From Rabbit Fed Normal Chowsupporting
confidence: 91%
“…Endogenous defense mechanisms may lead to failure with overproduction of free radicals and consumption of antioxidants. MDA, an oxidation product of polyunsaturated fatty acids, was accepted as a proven marker of lipid peroxidation [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Besides, the result of magnetic resonance imaging analysis in the kidneys of HCD-induced mice revealed renal dysfunction [ 49 ]. The increase in serum urea could be due to the consumption of HCD, which generates oxidant load and causes peroxidation, thereby leading to derangements in the rabbit kidney tissue [ 50 ].…”
Section: Discussionmentioning
confidence: 99%